NUTRINAL ASSESSMENT OF HYPERTENSIVE PATIENTS: A STUDY ON DIETARY PATTERNS AND LIFESTYLE HABIT (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Hypertension is now a growing world health issue especially in the developing world that is facing rapid urbanization, including the Hisar District of North India. This research aimed to assess the nutritional status, feeding practices, and lifestyle characteristics of hypertensive patients in the urban and rural areas of the district. The aim is to determine how these factors affect hypertension epidemiology and its control across various socio-economic settings.Methodologically a survey using close ended questionnaires were conducted online with 100 respondents from both urban and rural background. Anthropometric measurements, dietary and physical activity records and knowledge of participants regarding possible causes of hypertension were gathered using validated tools.Still findings reveal significant differences in nutritional status and health behaviors between the rural and urban dwellers. The results indicated that urban dwellers had higher levels of dietary risks and physical inactivity while rural areas presented unique eating habits and behaviors due to cultural factors and more physically active lifestyles. The distribution of etiological factors that predispose participants to hypertension also differed.They concluded that care plans which targeted aspects of diet and lifestyle unique to the regions were crucial for hypertension control. Thus, this research highlights the need for relevant health interventions to reduce the incidence of hypertension and enhance cardiovascular health in different socio-economic and environmental settings across Hisar District and other similar areas of the world.